2019
DOI: 10.1038/s41598-019-47287-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual dose-dependent effects of fingolimod in a mouse model of Alzheimer’s disease

Abstract: Lipid metabolism is abnormal in Alzheimer’s disease (AD) brain leading to ceramide and sphingosine accumulation and reduced levels of brain sphingosine-1-phosphate (S1P). We hypothesize that changes in S1P signaling are central to the inflammatory and immune-pathogenesis of AD and the therapeutic benefits of fingolimod, a structural analog of sphingosine that is FDA approved for the treatment of multiple sclerosis. We recently reported that the neuroprotective effects of fingolimod in 5xFAD transgenic AD mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 65 publications
1
41
0
1
Order By: Relevance
“…FTY720 treatment also increased the cell survival of neurons in co-culture with microglia on microfluidic chips and exposed to neurotoxic oligomers of amyloid-beta (Aβ) [81]. In support of a less inflammatory CNS environment, FTY720 also reduced the total brain Aβ-levels in a mouse model of AD [45], possibly via microglia cells which play a major role in the internalization and degradation of Aβ [82].…”
Section: Microgliamentioning
confidence: 97%
See 2 more Smart Citations
“…FTY720 treatment also increased the cell survival of neurons in co-culture with microglia on microfluidic chips and exposed to neurotoxic oligomers of amyloid-beta (Aβ) [81]. In support of a less inflammatory CNS environment, FTY720 also reduced the total brain Aβ-levels in a mouse model of AD [45], possibly via microglia cells which play a major role in the internalization and degradation of Aβ [82].…”
Section: Microgliamentioning
confidence: 97%
“…Both in vitro and in vivo studies have shown that FTY720 has inhibitory effects on the pro-inflammatory (M1) microglia phenotype and stimulates the anti-inflammatory (M2) microglia phenotype . In rodent models for several diseases, such as stroke, cuprizone-induced demyelination, MS (experimental autoimmune encephalitis, EAE), familial Alzheimer's disease (AD) and in irradiation-induced injury, FTY720 decreased microglia activation by polarization towards an anti-inflammatory M2 phenotype characterized by the increased expression of markers such as arginase 1 (ARG1) and mannose receptor C-type 1 (MRC1/CD206) [42][43][44] and a decreased microglia M1 state, defined by the expression of allograft inflammatory factor 1 (IBA1), cluster of differentiation 68 (CD68) and lysosome-associated membrane protein 2 (LAMP-2; CD107b/MAC-3) [42,43,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]71] Consistent with these findings, in vitro FTY720 inhibited the expression of M1 microglia markers and promoted the M2 polarization of oxygen-glucose deprivation (OGD)-insulted microglia [55], photothrombotic stroke-derived primary microglia cultures [42] and white matter-derived microglia from an ischemia rat model [43] as well as in the microglia cell line N9 [63], and human and murine primary microglia cultures [65]. Moreover, FTY720 downregulated the mRNA expression of the pro-inflammatory cluster (e.g., C-C motif chemokine ligand (CCL)7, chemokine (C-X-C motif) ligand (CXCL)13 and CCL5) and upregulated genes in the anti-inflammatory cluster (e.g., granulocyte-macrophage colony-stimulating factor (GM-CSF), chitinase 3-like 3 (CHI3L3) and interleukin (IL)-10) in microglia cells from non-obese EAE mice [65].…”
Section: Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the increase in BDNF protein was shown to be inversely correlated with the drug concentration [11]. A low dosage of FTY720 was also reported to influence in vitro viability of neural stem cells [27] and recently, also to rescue memory impairment in a mouse model of Alzheimer's disease [28]. Thus, we next tested the activity of a 5-fold lower concentration of FTY720-P in modulating the dendritic architecture of hippocampal neurons in primary hippocampal cultures.…”
Section: Fingolimod-phosphate (Fty720-p) Mediated Effects Are Bdnf-dementioning
confidence: 98%
“…Later studies indicated that the numbers of GABA inhibitory interneurons in the hippocampus were significantly decreased in transgenic mice such as TgCRND8, Tg2576, 5xFAD, and TauPS2APP (Krantic et al, 2012;Loreth et al, 2012;Verret et al, 2012;Flanigan et al, 2014;Huh et al, 2016;Palop and Mucke, 2016;Shu et al, 2016;Cattaud et al, 2018;Lerdkrai et al, 2018;Carreras et al, 2019; Table 2). Loss of PV and CR interneurons in the hippocampal CA1 of aged 3xTg-AD mice might be in part due to the global network excitability defects associated with AD (Zallo et al, 2018).…”
Section: Targeting Increased Numbers Of Gaba Inhibitory Interneuronsmentioning
confidence: 99%